2002
DOI: 10.1037/0022-006x.70.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting relapse back to smoking: Contrasting affective and physical models of dependence.

Abstract: Traditional models of physical dependence suggest that nicotine dependence should be reflected by the extent of drug exposure (e.g., smoking rate) and by evidence of physiological adaptation (e.g., withdrawal severity). An affective model suggests that nicotine dependence should be related to an individual's tendency to experience negative affect and expectations that nicotine use would ameliorate such affect. This research investigated the ability of these 2 models to predict relapse back to smoking at 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
2
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(233 citation statements)
references
References 80 publications
14
200
2
11
Order By: Relevance
“…Participants rate adjectives describing affective states on a scale of 1-5 using a specified time period (eg now, today and past week). The PANAS has been shown to be sensitive to the affective symptoms of tobacco withdrawal (Kenford et al, 2002).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Participants rate adjectives describing affective states on a scale of 1-5 using a specified time period (eg now, today and past week). The PANAS has been shown to be sensitive to the affective symptoms of tobacco withdrawal (Kenford et al, 2002).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…One of the important reinforcing qualities of smoking is its effects in managing negative affect (Gilbert 1995;Kassel et al 2003) and studies have demonstrated that nicotine reduces reports of anger (Jamner et al 1999). Also, smokers who experience anger situations are likely to increase their smoking behaviors (Jamner et al 1999;Kalman 2002;Kenford et al 2002). However, the extent to which negative affect influences smoking behavior is highly variable between individuals and is influenced by various situational factors (Gilbert 1995;Abrams et al 1988;Gilbert et al 2002;Hughes et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This duration was determined based on evidence in the literature that nicotine withdrawal-related cognitive decrements can appear as early as 4 hours, and peak within 48 hours, of abstinence initiation [18,19], symptoms are greatest at the earliest points of abstinence [20] and timing and severity of symptoms may be particularly salient to the establishment of long term abstinence [21,22]. The intent of this study was to characterize tobacco abstinence effects in adolescent smokers in a controlled environment and to differentiate these effects from normal variations related to typical adolescent lability.…”
Section: Nih Public Accessmentioning
confidence: 99%